Odontogenic facial swelling of unknown origin. (December 2015) - Ranjitkar, S; Cheung, W; Yong, R; Deverell, J; Packianathan, M; Hall, C
Abstract: Background: Current radiography techniques have limitations in detecting subtle odontogenic anomalies or defects that can lead to dentoalveolar and facial infections. This report examines the application of micro‐CT imaging on two extracted teeth to enable detailed visualization of subtle odontogenic defects that had given rise to facial swelling. Methods: Two extracted non‐carious mandibular left primary canine teeth (73) associated with odontogenic infections were selected from two patients, and an intact contralateral tooth (83) from one of the patients was used as a control. All three teeth were subjected to three‐dimensional micro‐CT imaging at a resolution of 20 μm. Results: Tooth 73 from the first case displayed dentine pores (channels) that established communication between the pulp chamber and the exposed dentine surface. In comparison, tooth 73 from the second case had a major vertical crack extending from the external enamel surface into the pulp chamber. The control tooth did not display any anomalies or major cracks. Conclusions: The scope of micro‐CT imaging can be extended from current in vitro applications to establish post‐extraction diagnosis of subtle odontogenic defects, in a manner similar to deriving histopathological diagnoses in extracted teeth. Ongoing technological advancements hold the promise for more widespread translatory applications.